„Uparte trwanie baroku” w recepcji wierszy Stanisława Barańczaka - Lisak-Gębala, Dobrawa (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
The article focuses on the functioning of the term ‘baroque’ in the reception of Stanisław Barańczak’s poems. The author takes into account the context of fashion for returning to the legacy of the baroque which became visible after 1956 in both poetry itself and in the discourse of both literary criticism and literary studies.